Pengaruh Pemberian Massage Effleurage Untuk Mengurangi Nyeri Dismenore Pada Remaja Putri - Irma Maya Puspita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: Dysmenorrhea is pain women feel in the lower abdomen before or during menstruation. Dysmenorrhea is divided into 2, namely primary dysmenorrhea and secondary dysmenorrhea. Primary dysmenorrhea is menstrual pain caused by myometrium contraction due to prostaglandins' production. Secondary dysmenorrhea is menstrual pain due to pathological abnormalities in the pelvis. In Indonesia, 43-93% of dysmenorrhea sufferers are young women. One method that can be used to reduce dysmenorrhea pain is massage effleurage. This study aimed to determine the effect of giving massage effleurage to decrease the intensity of dysmenorrhea pain in adolescent girls at adolescent girls in the working area of the Tanah Kali Kedinding Health Center Surabaya.Methods: This study uses a Quasi Experiment design with the Non-Equivalent Control Group Design type. The sample in this study was 22 people. The sample was divided into four action groups, namely experimental group 1 and experimental 2, which were given massage effleurage, and control groups 1 and 2 were not given any treatment. Experimental group 1 and experimental two were given treatment for 15 minutes and 10 minutes. The most effective action in reducing the intensity of dysmenorrhea pain is massage effleurage for 15 minutes.Results: The mean value of the Two Way Anova test is 3.83, and the significance value for the time variable is 0.015 (significant).Conclusion: Based on the study’s results, it is recommended for young women to apply the massage effleurage method because it can be done quickly so that they can carry out daily activities well when experiencing dysmenorrhea